The Effect Of Obesity On Diabetic Ulcers In Diabetes Mellitus Patients - Muhammad Salman Naguib; Pratiwi Nasir Hamzah; Nur Nasri Arsyad (Sean Institute, 2024)
Diabetes mellitus ( DM ) is disease metabolic characterized with hyperglycemia Because lack of insulin secretion, insulin action, or both of them. Diabetes was diagnosed when blood sugar fasting >126 mg/dL and 2-hour blood sugar >200 mg/dL. Diabetic foot ulcers is one of complications chronic from Diabetes mellitus (DM) disease in the form of surface wound skin of the feet of diabetics accompanied by with damage network part in or death network. Risk factors can influence incident DM ulcers are cigarettes, obesity, increasing work physique especially in men. Method: Review literature review using Google Scholar, National Center for Biotechnology Information (NCBI) & Research Science 20 journals obtained from criteria inclusion & exclusion. Results: Complications ulcer diabetic in patients with diabetes mellitus type 2 is one of the the most cases treated at home sick. There are several modifiable factors, including obesity. Condition obesity can cause insulin resistance which results in atherosclerosis so that happen disturbance circulation blood in the legs that can cause ulcer diabetic. Conclusion: Risk factors can influence incident DM ulcers are obesity, condition obesity can cause insulin resistance which results in atherosclerosis so that happen disturbance circulation blood in the legs that can cause ulcer diabetic.